A Washing-Free and Easy-to-Operate Fluorescent Biosensor for Highly Efficient Detection of Breast Cancer-Derived Exosomes - Chen, Wenqin; Zhang, Yan; Di, Kaili; Liu, Chang; Xia, Yanyan; Ding, Shijia; Shen, Han; Li, Zhiyang (Frontiers in Bioengineering and Biotechnology, 2022)
Traditional detection methods for protein tumor markers in the early screening of breast cancer are restricted by complicated operation procedures and unstable reproducibility. As one of alternative emerging tumor markers, exosomes play an important role in diagnosing and treating cancers at the early stage due to traceability of their origins and great involvement in occurrence and development of cancers. Herein, a washing-free and efficient fluorescent biosensor has been proposed to realize simple and straightforward analysis of breast cancer cell-derived exosomes based on high affinity aptamers and G quadruplex-hemin (G4-hemin). The whole reaction process can be completed by several simple steps, which realizes washing-free and labor-saving. With simplified operation procedures and high repeatability, the linear detection range for this developed fluorescent biosensing strategy to breast cancer cell-derived exosomes is from 2.5 × 105 to 1.00 × 107 particles/mL, and the limit of detection is down to 0.54 × 105 particles/mL.